Ultra-broadband thermal radiator for daytime passive radiative cooling based on single dielectric SiO2 on metal Ag. (November 2022) - Li, Yulian; Gao, Wei; Li, Linzhi; Guo, Li; Ge, Haonan; Xie, Runzhang; Wang, Hao; Wang, Fang; An, Bowen
Abstract: Passive radiative cooling plays an essential role in global energy conservation and environment preservation. We designed a single medium cone SiO2 on Ag, which reflects more than 96% sunlight and emits near-unity infrared between 8 – 25 μ m . Under direct sunlight of 10 3 W/m 2, the designed cooler can effectively achieve a predicted steady-state temperature of 261 K, which is 39 K below ambient at 300 K without consideration of thermal convection and conduction. When considering the significant influence of external conduction and convection (10 W/m 2 /K), the net cooling power of the cooler is about 121 W/m 2 at T = 300 K, and the predicted steady-state temperature is 9 K below ambient. When sunlight is shielded, the net cooling power is 160 W/m 2 and the predicted steady-state temperature is 244 K at h c = 0 W/m 2 /K and 288 K at h c = 10 W/m 2 /K. It benefits from the zero transmission of Ag, the particular extinction coefficient of SiO2 and the optimized structure. Furthermore, we explored the inner mechanism through studying the dependences of spectra on structure, geometry parameters as well as electromagnetic field distributions. The excellent performances of passive cooling with simple and compatible structure and mature SiO2 can effectively enhance the efficiency of the cooling system, and promote the practical application for radiative cooling greatly.